ACUTE TOXICITY WATER EXTRACT OF Meretrix meretrix Linnaeus IN VIVO ON SPRAGUE DAWLEY RATS - Apriandi, Azwin; Tarman, Kustiariyah; Sugita, Purwantiningsi (Asian Journal of Aquatic Sciences, 2021)
Meretrix meretrix empirically has been widely believed by the public to a wide variety of health benefits. It is necessary to do an analysis of the level of toxicity of Meretrix meretrix extract. The experiment was carried out extraction sample with water (1;4) (w/v), analysis of acute toxicity Meretrix meretrix extract with the OECD method 403:2009. Based on the results of water extract of Meretrix meretrix no effect on physical observations of test animals with LD50> 15 g/kg BW. Histopathological observation on the liver and kidneys, there is necrosis of the liver cells and some cell degeneration in the kidneys, but on the whole network under normal conditions appropriate control group.